THE PERFORMANCE OF CERTIFIED AND NON-CERTIFIED TEACHERS IN IMPROVING LEARNING QUALITY OF STATE JUNIOR HIGH SCHOOLS IN SAMATIGA DISTRICT - Marlina Dahlan; Siti Mayang Sari; Akmaluddin (International Conference on Education, Science, Technology and Health (ICONESTH), 2023)
This research aims to determine the performance of certified and non-certified teachers in improving learning quality of State Junior High Schools (SMPN) in Samatiga District, West Aceh. This research uses a quantitative approach, the research sample is 15 people. Data collection techniques were carried out using questionnaires and documentation. Based on the research results, it is known that certified teachers in improving learning quality of State Junior High Schools in Samatiga District, West Aceh, seen from the aspects of professional, pedagogical and social competence, are quite good, even personality competence is classified as good. Non-certified teachers in improving learning quality of State Junior High Schools throughout Samatiga District, West Aceh, seen from the aspects of professional, pedagogical and social competence, are quite good. However, personality competence is still relatively lacking.